School and workplace sarpras influence on the performance of kindergarten teacher - Juliana S; Yasir Arafat; Syaiful Eddy (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
Research aims to understand influence infrastructure to school and workplace on teacher performance. The study was conducted in Plakat Tinggi Musi Banyuasin district.Type this research is quantitative research with the design penetian use design this research expost facto capital.Included in this study was a total all teachers in public primary schools as TK in plakat tinggi district consisting of 50 the teachers. Technique use survey data collection, dokumetasi and observation. Data analysis technique using a technique descriptive analysis kuantittaif, berganda and regression.Results stated that 1) is to influence infrastructure as a teacher tk kecamatan placard; 2) is high environmental influences work on teacher performance kindergarten to high as kecamatan placard; 3) is influence together to infrastructure and workplace tk on teacher performance as Plakat Tinggi kabupaten Musi Banyuasin.